Community-based health care is an essential component of a resilient health system: evidence from Ebola outbreak in Liberia. (December 2017) - Siekmans, Kendra; Sohani, Salim; Boima, Tamba; Koffa, Florence; Basil, Luay; Laaziz, Saïd
Abstract Background Trained community health workers (CHW) enhance access to essential primary health care services in contexts where the health system lacks capacity to adequately deliver them. In Liberia, the Ebola outbreak further disrupted health system function. The objective of this study is to examine the value of a community-based health system in ensuring continued treatment of child illnesses during the outbreak and the role that CHWs had in Ebola prevention activities. Methods A descriptive observational study design used mixed methods to collect data from CHWs (structured survey, n  = 60; focus group discussions, n  = 16), government health facility workers and project staff. Monthly data on child diarrhea and pneumonia treatment were gathered from CHW case registers and local health facility records. Results Coverage for community-based treatment of child diarrhea and pneumonia continued throughout the outbreak in project areas. A slight decrease in cases treated during the height of the outbreak, from 50 to 28% of registers with at least one treatment per month, was attributed to directives not to touch others, lack of essential medicines and fear of contracting Ebola. In a climate of distrust, where health workers were reluctant to treat patients, sick people were afraid to self-identify and caregivers were afraid to take children to the clinic, CHWs were a trusted source of advice and Ebola prevention education. These findings reaffirm the value of recruiting and training local workers who are trusted by the community and understand the social and cultural complexities of this relationship. "No touch" integrated community case management (iCCM) guidelines distributed at the height of the outbreak gave CHWs renewed confidence in assessing and treating sick children. Conclusions Investments in community-based health service delivery contributed to continued access to lifesaving treatment for child pneumonia and diarrhea during the Ebola outbreak, making communities more resilient when facility-based health services were impacted by the crisis. To maximize the effectiveness of these interventions during a crisis, proactive training of CHWs in infection prevention and "no touch" iCCM guidelines, strengthening drug supply chain management and finding alternative ways to provide supportive supervision when movements are restricted are recommended.